Quantitative and dynamic measurements of biological fresh samples with X‐ray phase contrast tomography. (7th October 2014) - Hoshino, Masato; Uesugi, Kentaro; Tsukube, Takuro; Yagi, Naoto
<x xml:space="preserve">Abstract</x> X‐ray phase contrast tomography using a Talbot grating interferometer was applied to biological fresh samples which were not fixed by any fixatives. To achieve a high‐throughput measurement for the fresh samples the X‐ray phase contrast tomography measurement procedure was improved. The three‐dimensional structure of a fresh mouse fetus was clearly depicted as a mass density map using X‐ray phase contrast tomography. The mouse fetus measured in the fresh state was then fixed by formalin and measured in the fixed state. The influence of the formalin fixation on soft tissue was quantitatively evaluated by comparing the fresh and fixed samples. X‐ray phase contrast tomography was also applied to the dynamic measurement of a biological fresh sample. Morphological changes of a ring‐shaped fresh pig aorta were measured tomographically under different degrees of stretching.